Slang Language of Youth Generation Z Southwest Papua: Morphology Review - Hermawan, Adi Iwan; Faizin, Muhammad (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Slang is also referred to as a secret language, or used by certain circles or communities. The purpose of this study is to examine slang based on patterns, sources, context and purpose of use. This study uses qualitative descriptive research, which describes the phenomenon of slang used by gen z adolescents in Southwest Papua. Documentation, observation, recording, and interviews with 35 teenagers who regularly use slang are used as data gathering techniques. Documentation, observation, recording, and interviews with 35 teenagers who regularly use slang are used as data gathering techniques. WhatsApp, Telegram, Twitter, and Discord are used as data sources. The period of data collecting was five months, from October 12, 2022, to February 12, 2023. The data that has been collected is then analyzed using the Miles and Huberman method. According to the findings of data analysis on slang, there were 31 discovered three types, namely the development of form. (1) clipping, (2) blending, (3) borrowing. The results of the data analysis revealed a variety of information on Southwest Papuan slang used by Generation Z based on the language's origins, particularly Indonesian, foreign languages, and regional languages. The context of slang use takes place in (1) Calls for familiarity, (2) responding to likes and dislikes, and (3) responding to admiration. the purpose of using the slang they use to (1) validate their group (2) look cool or dashing